4DCT and VMAT for lung patients with irregular breathing. Issue 1 (24th November 2021) - Caines, Rhydian; Sisson, Naomi K.; Rowbottom, Carl G.
Abstract: Purpose: Irregular breathing in lung cancer patients is a common contra‐indication to 4D computerized tomography (4DCT), which may then limit radiotherapy treatment options. For irregular breathers, we investigated whether 3DCT or 4DCT (1) better represents tumor motion, (2) better represents average tumor densities, and (3) better allows for volumetric modulated arc threarpy (VMAT) plans delivered with acceptable dosimetric accuracy. Methods: Ten clinical breathing traces were identified with irregularities in phase and amplitude, and fed to a programmable moving platform incorporating an anthropomorphic lung tumor phantom. 3DCT and 4DCT data resorted by phase (4DCT‐P) and amplitude (4DCT‐A) were acquired for each trace. Tumors were delineated by Hounsfield unit (HU) thresholding and apparent motion range assessed. HU profiles were extracted from each image and agreement with calculated expected profiles quantified using area‐under‐curve (AUC) scoring. Clinically representative VMAT plans were created for each image, delivered to the irregularly moving phantom, and measured with a small‐volume ion chamber at the tumor center. Results: Median difference from expected tumor motion range for 3DCT, 4DCT‐P, and 4DCT‐A was 2.5 [1.6–3.6] cm, 1.1 [0.1–1.9] cm, and 1.3 [0.4–1.9] cm, respectively ( p  = 0.005, 4DCT‐P vs. 3DCT). Median AUC scores (ideal = 0) for 3DCT, 4DCT‐P, and 4DCT‐A were 0.25 [0.14–0.49], 0.12 [0.05–0.42], and 0.13 [0.09–0.44], respectively ( p  = 0.005, 4DCT‐P vs. 3DCT). Nine of ten 4DCT‐P plans and all 4DCT‐A plans measured within 2.5% of expected dose in the treatment planning system (TPS), compared with seven 3DCT plans. Conclusion: For the cases studied tumor motion range and average density was better represented with 4DCT compared with 3DCT, even in the presence of irregular breathing. 4DCT images allowed for delivery of VMAT plans with acceptable dosimetric accuracy. No significant differences were detected between phase and amplitude resorting. In combination with 4D cone beam imaging at treatment, our findings have given us confidence to introduce 4DCT and VMAT for lung radiotherapy patients with irregular breathing.